Answer:
x= 0 ; 2; 3
Explanation:
Let's solve your equation step-by-step.
![3x^(3) -15x^(2)+18x=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/riieqdlvkmluuhodzmzwu4zpilypj0xfy0.png)
Three x to the third power minus 15x to the second power + eighteen x equals 0.
Step 1: Factor left side of equation.
![3x(x-2)(x-3)=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wmibg88b6bex9md1i7e1fichyq618xhnqx.png)
Three x times x minus 2 times x minus three equals 0
Step 2: Set factors equal to 0.
![3x=0 ; x-2=0 ; x-3=0\\x=0 ; x=2 ; x=3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vnbfpljrymbcwjftnfl6mfku9zcv72nhgt.png)